The Interactions among the Heavy Metals in Soils and in Weeds and Their Antioxidant Capacity under the Mining Activities in Thai Nguyen Province, Vietnam - Ngoc-Lien Nguyen; Cam-Tu Vu; Hien-Minh To; Hoang-Nam Pham; Hai-Dang Nguyen; Tien-Dat Nguyen; Kieu-Oanh Nguyen Thi (Journal of Chemistry)
In this study, the relationship between heavy metals (HMs) concentrations in soils and several weeds including Cyclosorus parasiticus, Dicranopteris linearis, Pityrogramma calomelanos, and Pteris vittata in three mining sites (Cam Gia (Thai Nguyen city), Tan Long (Dong Hy district), and Ha Thuong (Dai Tu district)) in Thai Nguyen province, Vietnam, have been investigated. The levels of HMs varied among soil origins and showed the contaminations of As, Cu, and Pb in soil samples collected in Dong Hy and Dai Tu districts. In addition, the HM distribution and cocontamination phenomena in different soils significantly affected the HM residues and transportation abilities into different species as well as tissues. Moreover, based on the analysis of bioaccumulation factor (BF) and translocation factor (TF), C. parasiticus and D. linearis were found potentially for phytoextraction by roots, while P. calomelanos and P. vittata were suitable for hyperaccumulation in shoots and leaves. Consequently, the strongest antioxidant property by 1,1-diphenyl-2-picrylhydrazyl (DPPH) and superoxide anion (SRSA) radical scavenging assays were demonstrated in the methanol root extracts of C. parasiticus and P. vittata, respectively. In conclusion, the correlation among HM in soils and tissues with antioxidant property allows us to hypothesize that the presence of these elements can enhance the antioxidant activity of plant extracts, suggesting to apply the weeds in phytoremediation as well as in phytomedicine.